The burden of stress in head and neck cancer. Issue 3 (5th March 2012) - Devins, Gerald M.; Payne, Ada Y. M.; Lebel, Sophie; Mah, Kenneth; Lee, Ruth N. F.; Irish, Jonathan; Wong, Janice; Rodin, Gary M.
Abstract Background Head and neck cancer (HNCa) introduces numerous stressors. We developed the Cancer‐Related Stressors Checklist (CRSC), which documents exposure to seven categories of common stressors and emotional distress. We surveyed HNCa survivors and examined associations among exposure to cancer‐related stressors, illness intrusiveness (i.e., cancer‐induced interference with lifestyles, activities, and interests), and distress. We also investigated whether reported exposure rates differ between self‐administered and interviewer‐administered measures. Methods Respondents included HNCa survivors, stratified by sex, who participated in one of two clinical studies (N1 = 162; N2 = 408) examining the psychosocial impact of illness intrusiveness. All completed the CRSC, the Center for Epidemiologic Studies Depression Scale, and the Illness Intrusiveness Ratings Scale. Study 1 respondents self‐administered the instruments; an interviewer administered them in Study 2. We gathered clinical data by self‐report and from medical records. Results High inter‐rater reliability corroborated the 8‐subscale structure of the CRSC (Krippendorff alpha = .92). Cancer‐related stressor exposures differed significantly across categories (interpersonal stressors were most common). Controlling for empirically identified covariates and distress, exposure to each cancer‐related stressor correlated significantly and uniquely with illness intrusiveness. All stressor categories correlated significantly with distress, but coefficients were low to moderate, substantiating incremental validity. Respondents reported fewer exposures when materials were self‐administered as compared with interviewer‐administered, but reported distress levels did not differ by mode of administration. Conclusions Cancer‐related stressors are common and burdensome in HNCa and, therefore, merit clinical attention. Identifying specific stressors will allow more targeted and effective interventions to alleviate and prevent distress. Copyright © 2012 John Wiley & Sons, Ltd.